Ungulate use of non-wildlife underpasses. (1st November 2020) - Bhardwaj, Manisha; Olsson, Mattias; Seiler, Andreas
Abstract: Wildlife crossing structures can provide safe passage for wildlife across transportation corridors, and can help mitigate the effects of highways and exclusion fencing on wildlife. Due to their costs, wildlife crossing structures are usually installed sparsely and at strategic locations along transportation networks. Alternatively, non-wildlife underpasses (i.e. conventional underpasses for human and domestic animal use) are usually abundant along major infrastructure corridors and could potentially provide safe crossing opportunities for wildlife. To investigate this, we monitored the use of 40 non-wildlife underpasses by roe deer ( Capreolus capreolus ), and moose ( Alces alces ) in south-central Sweden. We found that roe deer and moose use non-wildlife underpasses, and prefer underpasses that are at least 11.5 m wide and 5 m tall. Furthermore, roe deer used structures that had little human co-use and were in locations where the forest cover differed on both sides of the highway. In most cases, roe deer and moose were detected within 50 m of the underpass more than they were detected crossing under them. This suggests that animals often approach underpasses without crossing under them, however modifications to underpass design may improve non-wildlife underpass use. We recommend non-wildlife underpasses at gravel and minor roads, particularly those with little human co-use and with variable forest cover on both sides of the highway, be built wider than 11.5 m and taller than 5 m. Highlights: Non-wildlife underpasses are actively used by roe deer and moose. Roe deer and moose tend to use underpasses with little human use and variable forest cover on both sides of the road. Underpasses that are at least 11.5 m wide and 5 m tall are likely used by roe deer and moose. Non-wildlife underpasses may supplement connectivity provided by wildlife crossing-structures.